Thinking with Adorno : The Uncoercive Gaze - Richter, Gerhard, 1967- (Book collections on Project MUSE., 2019)
This book argues that the work of Theodor W. Adorno is best understood through the lens of his highly suggestive--yet often overlooked--concept of the ""uncoercive gaze, "" an innovative way of relating to the object of one's analysis that interweaves critical intimacy and analytic vigilance